2019
DOI: 10.1021/jacs.8b11912
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Thiophosphorodichloridate Reagents for Chemoselective Histidine Bioconjugation

Abstract: Site-selective bioconjugation to native protein residues is a powerful tool for protein functionalization, with cysteine and lysine side chains being the most common points for attachment owing to their high nucleophilicity. We now report a strategy for histidine modification using thiophosphorodichloridate reagents that mimic post-translational histidine phosphorylation, enabling fast and selective labeling of protein histidines under mild conditions where various payloads can be introduced via copper-assiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 68 publications
0
94
0
3
Order By: Relevance
“…The profiling of amino acid reactivity within proteins is a rapidly expanding field, with this chemical proteomic strategy having been successfully applied to profile the reactivity of serine (Kidd et al , ), cysteine (Weerapana et al , ), lysine (Hacker et al , ), histidine (Jia et al , ), tyrosine (Hahm et al , ) and methionine residues (Ohata et al , ). A method to efficiently prioritize these reactive sites according to their contribution to protein function would optimize pipelines for target‐based screening platforms.…”
Section: Resultsmentioning
confidence: 99%
“…The profiling of amino acid reactivity within proteins is a rapidly expanding field, with this chemical proteomic strategy having been successfully applied to profile the reactivity of serine (Kidd et al , ), cysteine (Weerapana et al , ), lysine (Hacker et al , ), histidine (Jia et al , ), tyrosine (Hahm et al , ) and methionine residues (Ohata et al , ). A method to efficiently prioritize these reactive sites according to their contribution to protein function would optimize pipelines for target‐based screening platforms.…”
Section: Resultsmentioning
confidence: 99%
“…[323][324][325][326][327][328][329] Richtungweisend dafüri st die Entwicklung einer Chemoproteomikplattform zur Identifizierung hyperreaktiver Cysteine durch isoTOP-ABPP (isotopic Tandem Orthogonal Proteolysis -A ctivity-Based Protein Profiling). [330] Aufbauend auf umfangreichen ABPP-Arbeiten über Cystein-, [331,332] Lysin- [333,334] und Serinnachweise [335] haben wir und andere Biokonjugationsstrategien fürw eitere native Aminosäuren verfolgt, darunter Methionin, [336][337][338] Histidin, [339] Ty rosin [340][341][342] und Tryptophan. [343] So haben unser Labor und Tostes Arbeitsgruppe gemeinsam eine neue ABS-Methode fürd ie Methionin-Biokonjugation entwickelt, genannt ReACT (Redox-Activated Chemical Tagging), bei der wir die nativen Redoxeigenschaften der Oxidation von Methionin zu Methioninsulfoxid nutzen, um Oxaziridinreagenzien zu entwickeln, die die isoelektronische Nitrenübertragung zu einem Sulfimidaddukt auslçsen.…”
Section: Angewandte Chemieunclassified
“…These efforts have been extensively reviewed. [1][2][3][4][5] More recently, several more of these methods have been reported that utilize novel functional groups to demonstrate impressive chemoselectivity to Cys, [6][7][8][9] Lys, [10][11][12][13] His, [14][15][16] Met, [17][18][19] Trp, [20] and Tyr. [21] Relatedly, dehydroalanine (Dha)-mediated modification is an indirect but notable approach.…”
Section: Functional Group Innate Reactionsmentioning
confidence: 99%